Concrete as a factor in reinforced concrete buildings collapse in Burundi - E. Mikerego; J. Ndikumana (Вестник СибАДИ, 2022)
Introduction. This paper presents the results of the assessment in-situ of the involvement of the concrete in the collapse of reinforced concrete buildings in Burundi.Materials and Methods. The study consisted in the identification of the compressive strengths of the concrete structural elements of the reinforced concrete buildings under study. The compressive strengths were identified on the columns, beams and slabs using an industrial SCHMIDT 2000 sclerometer according to the protocol described in NF EN 12504-2(2003). Seventeen (17) three-storey buildings under construction were studied. For each building involved in the study, the reinforced concrete bearing elements of the first floor were studied. The results obtained were classified according to the cement grades (32.5) and (42.5) that were used in the studied buildings. A comparison of the compressive strengths obtained in-situ was established in relation to the normative values according to the cement grade used. The reliability of the obtained results was confirmed by the correlation between the results obtained in the laboratory conditions on the reinforced concrete experimental samples.Results. This study showed that in Burundi up to 100% of collapses are caused by privately built structures. It was proved that the compressive strengths of 100% of the columns, 82% of the beams and 82% of the slabs that were made with a low-grade cement (32.5) had compressive strengths lower than the normative value (25MPa). In addition, the compressive strengths of 50% of the columns, 50% of the beams and 84% of the slabs made with a high-grade cement (42.5) were also proved to have compressive strengths lower than the normative values (35MPa).Discussion and conclusion. In this study, the reliability of the results obtained by sclerometer test in-situ on the reinforced concrete buildings has been proved. Concrete has been shown to be a factor in the collapse of privately built reinforced concrete buildings in Burundi. Low-grade cement was observed to have a high impact in the collapse of reinforced concrete structures than the high-grade one. Therefore, as a recommendation, the process of building reinforced concrete buildings in Burundi needs to be regulated and controlled.